1995
DOI: 10.1007/bf01262332
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor ?1 inhibits IL-3- and IL-4-dependent mouse connective tissue-type mast cell proliferation

Abstract: Transforming growth factor beta 1 (TGF beta 1) is a regulator of cell proliferation and differentiation. Using a mouse peritoneal cell-derived mast cell culture system, we investigated the effects of TGF beta 1 on mast cell proliferation. TGF beta 1 inhibited IL-3- and IL-4-dependent connective tissue-type mast cell proliferation. The effect was concentration dependent: 50% inhibition was observed with 1.0 ng/ml TGF beta 1 and the maximal inhibitory effect (no proliferation), was observed with 10 ng/ml. Flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Previous reports on the effects of TGF-b1 in MC were mostly restricted to the murine system. [19][20][21][22][23][24] Such data cannot be transferred easily to the human system because of the well documented heterogeneity of MC derived from different species and body sites. 10 Moreover, most studies only examined TGF-b1 effects on MC proliferation, not on mediator release, the main effector function of MC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports on the effects of TGF-b1 in MC were mostly restricted to the murine system. [19][20][21][22][23][24] Such data cannot be transferred easily to the human system because of the well documented heterogeneity of MC derived from different species and body sites. 10 Moreover, most studies only examined TGF-b1 effects on MC proliferation, not on mediator release, the main effector function of MC.…”
Section: Discussionmentioning
confidence: 99%
“…In the murine system, TGF-b1 has been proposed as an inhibitor of MC growth. [19][20][21][22] Whether TGF-b1 also regulates MC mediator release is unclear as experiments in mice yielded conflicting results. [21][22][23][24] In humans, no data are available as yet but TGF-b1 may also affect human MC functions, as reported by Olsson et al who found that TGF-b1 has chemotactic and growth inhibitory effects in the immature human leukaemic mast cell line HMC-1 and in human cord blood derived MC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some additional cytokines promote mast cell growth and survival, notably interleukin (IL)-3, IL-4, and IL-9, which are synthesized during the course of parasite infections and in allergic disease. Others, such as IL-10 and transforming growth factor (TGF)-β, counteract mast cell growth and activation (Broide, Wasserman, Alvaro-Gracia, Zvaifler, & Firestein, 1989;Shelburne & Ryan, 2001;Toyota, Hashimoto, Matsuo, & Iizuka, 1995). IL-3 is a major contributor to mast cell expansion in murine helminth infection (Lantz et al, 1998), but human mast cells do not universally respond to IL-3 (Gebhardt et al, 2002;Valent et al, 1990).…”
Section: Mast Cell Homeostasismentioning
confidence: 94%
“…We and others have shown that TGFβ1- and IL-10 serve as autocrine and paracrine regulators of the mast cell response [37; 48; 49; 50; 51; 52; 53; 54; 55; 56; 57; 58; 59; 60; 61; 62; 63], including protease expression [32; 33; 64; 65] and migration [34; 35; 36]. The suppressive effects of TGFβ1 and IL-10 we have previously reported require approximately 3 days to manifest [31; 50; 58; 66], fitting the kinetics of ADAM10 downregulation.…”
Section: Discussionmentioning
confidence: 99%